TANTANGAN DAN PELUANG KARIR PADA REVOLUSI INDUSTRI 4.0 UNTUK PROFESIONAL TI (INFORMATION TECHNOLOGY) PADA ABAD KE-21 - Harta Putra, Syaflan Sandi; Giatman, M.; Syah, Nurhasan (Ensiklopedia of Journal, 2022)
The Industrial Revolution 4.0 has now taken over almost most of the economic activities, many areas of human life including the world of work and even the human lifestyle itself. The Industrial Revolution 4.0 combines machines, workflows and systems with the application of artificial intelligence throughout the process. A very big threat occurs if we cannot keep up with technological advances in this era, we will be run over by technological advances. The Industrial Revolution 4.0 will revolutionize the movement of the world economy. If we don't prepare now, we will be far behind in the world economy. Industry 4.0 applies more technology, the role of workers is still needed. To achieve business success in the digital era, a well-formed ecosystem and communication are needed by business people. So that a strong and mutually beneficial ecosystem is achieved. Keywords: Industrial Revolution, Teknology, Human Resource, Network, Internet